Alkali doped poly (2,5-benzimidazole) membrane for alkaline water electrolysis: Characterization and performance - Díaz, Liliana Alicia (2016)
The properties and performance of linear and cross-linked KOH doped ABPBI membranes as electrolyte/separator for zero gap alkaline water electrolysis cells are evaluated and compared with a commercial Zirfon® diaphragm. Stability in alkaline environment, swelling, thermal properties, water sorption, KOH uptake and conductivity of linear (L-ABPBI) and cross-linked (C-ABPBI) membranes doped with different concentrations of KOH are analyzed. Linear membranes show stability up to 3.0 mol·dm−3 KOH doping, while cross-linked membranes are stable up to 4.2 mol·dm−3 KOH doping. Both kinds of membranes exhibit good thermal stability and reasonable specific ionic conductivity at 22 °C in the range between 7 and 25 mS·cm−1, being slightly higher the conductivity of C-ABPBI membranes than that of L-ABPBI ones. In short-term electrolysis tests both L-ABPBI and C-ABPBI membranes show better performance than Zirfon diaphragm in the range from 50 to 70 °C. A current density of 335 mA·cm−2 at a cell voltage of 2.0 V is attained with C-ABPBI membranes doped in 3 mol·dm−3 KOH at 70 °C, a performance comparable with that of commercial units operating at temperatures ca. 80 °C and 30 wt% KOH (6.7 mol·dm−3) as electrolyte.